2022
DOI: 10.18633/biotecnia.v25i1.1680
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant activity and cytotoxicity of flower extracts from Magnolia grandiflora L. found in southeast Mexico

Abstract: Many reports state that different structures of M. grandiflora contain bioactive components. Nonetheless, phytochemical studies reported that the extracted essential oils are chemically different and remarkably variable in their qualitative and quantitative compositions. Further studies Mexican M. grandiflora needs to be done. Thus, the research aimed to characterize a) the chemical composition, b) the antioxidant activity and c) cytotoxicity effect of two M. grandiflora flower extracts. The chemical compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Studies reported polyphenols levels, ranging from 14 mg/g to 17 mg/g, between 86 mg GAE/g and 192 mg GAE/g, at 46.8 mg GAE/g, with variations depending on factors like moisture and temperature. The antioxidant activity in these studies recorded to range between 84 and 311 mg VCE/g MFE, or was 54.5µg/mL (DPPH/IC50), 459.6µmol TE/g (ABTS), thus demonstrating the significant antioxidant potential of Magnolia species [21][22][23].…”
Section: Discussionmentioning
confidence: 75%
“…Studies reported polyphenols levels, ranging from 14 mg/g to 17 mg/g, between 86 mg GAE/g and 192 mg GAE/g, at 46.8 mg GAE/g, with variations depending on factors like moisture and temperature. The antioxidant activity in these studies recorded to range between 84 and 311 mg VCE/g MFE, or was 54.5µg/mL (DPPH/IC50), 459.6µmol TE/g (ABTS), thus demonstrating the significant antioxidant potential of Magnolia species [21][22][23].…”
Section: Discussionmentioning
confidence: 75%